2020
DOI: 10.1007/s11420-020-09808-x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Telehealth for the Treatment of Spinal Disorders: Patient-Reported Experiences During the COVID-19 Pandemic

Abstract: Background The use of telehealth saw a rapid surge during the early months of the COVID-19 pandemic. There remains little data on how effectively telehealth replicates traditional office visits in the treatment of spinal disorders and how telehealth is perceived by patients with spinal disorders. Questions/Purposes We sought to evaluate patient satisfaction with telehealth visits as a platform for delivering care for the treatment of spinal pathology. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…[1][2][3] Spine patients have generally been very satisfied with telemedicine visits and have rated them highly for the clarity of communication, formulation of treatment plans, and the ability to ask questions. [9][10][11] Due to such rapid introduction of the technology as well as changing medical, political, and legal landscapes, several uncertainties surrounding the optimal utilization of telemedicine in spine surgery persist. 12 Previous studies have shown considerable differences in the definition of telemedicine across geographic regions (e.g., telephone visits vs. video visits).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Spine patients have generally been very satisfied with telemedicine visits and have rated them highly for the clarity of communication, formulation of treatment plans, and the ability to ask questions. [9][10][11] Due to such rapid introduction of the technology as well as changing medical, political, and legal landscapes, several uncertainties surrounding the optimal utilization of telemedicine in spine surgery persist. 12 Previous studies have shown considerable differences in the definition of telemedicine across geographic regions (e.g., telephone visits vs. video visits).…”
Section: Discussionmentioning
confidence: 99%
“…Haddas et al [82] reported that cameras and gait analysis platforms have described patterns of gait dysfunction caused by conditions such as myelopathy. In addition, patients who receive telemedicine for spine-related complaints have given high ratings for overall satisfaction and ease of use [85].…”
Section: Medical Examinationmentioning
confidence: 99%
“…Although telemedicine spread rapidly during the COVID-19 pandemic, it has not yet been determined how best to perform an objective physical examination of the spine in the remote setting [85]. The limitations of telemedicine in performing a physical examination or collecting proper manual neurological findings in the field of spine medicine have been the biggest obstacle to adoption by spinal surgeons [85].…”
Section: Medical Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Though historically underutilized in orthopedics due to legislative barriers, technological limitations, and physician hesitation, 1 telemedicine's efficacy, [2][3][4][5] cost-effectiveness, [6][7][8][9][10] and high levels of patient satisfaction 3,[10][11][12][13][14] have been demonstrated in emerging literature. More recently, within in the realm of spine care, telemedicine was shown to be both safe and effective, [15][16][17] and groups began proposing standardized virtual neurologic exams. [18][19][20][21] Furthermore, telemedicinebased spine surgical plans were found to be accurate.…”
mentioning
confidence: 99%